The aesthetics of the sublime in the section El Jorullo in the Rusticatio Mexicana - Cuvardic García, Dorde (2013)
This essay presents an analysis, based on theaesthetics of the sublime, of the work Rusticatio Mexicana(1782), Section II, from Guatemalan writer RafaelLandivar (1731-1793). The narrative on the eruption of Jorullo Volcano follows the standard procedures of clas-sicism, but also contributes to the representation of theuniqueness of America. In this contribution one candetect elements of sensist philosophy, as well as catego-rizations that can be analyzed by the aesthetic theoriesof sublimity (Addison, Burke, Kant), which highlight thehuman experience of the sublime, which is observed inthe spectacular nature, in contrast to the experience ofbeauty, noticeable in the human work of art.